Biomanufacturing Seamless Tubular and Hollow Collagen Scaffolds with Unique Design Features and Biomechanical Properties. Issue 5 (30th January 2017) - Singh, Anirudha; Lee, David; Sopko, Nikolai; Matsui, Hotaka; Sabnekar, Praveena; Liu, Xiaopu; Elisseeff, Jennifer; Schoenberg, Mark P.; Pienta, Kenneth; Bivalacqua, Trinity J.
Abstract : A versatile process to develop designer collagen scaffolds for hollow and tubular tissue engineering applications is presented. This process creates seamless and biomechanically tunable scaffolds ranging from ureter‐like microsized tubings to structures with highly customized lumens that resemble intestinal villi, fluid bladders, and alveolar sacs that together with stem cells can potentially be used in preclinical and clinical settings.